2020
DOI: 10.14302/issn.2641-4538.jphi-20-3437
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Recovery among Children with Moderate Acute Malnutrition Treated at Kirehe District Health Centers

Abstract: Acute malnutrition affects nearly 52 million of under five years children globally, 75% of them live in low to middle income countries. The treatment of acute malnutrition using supplement foods could help children recovering and could reduce the risk of sickness. The present study investigated the factors associated with recovery among children with moderate acute malnutrition (MAM) under a follow-up program at health facilities. A prospective study was conducted in 16 health centers of Kirehe District of Rwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Children who were not dewormed were 1.87 times (AHR = 1.87, 95%CI: 1.34–2.61) more likely to recover faster than their counterparts. The finding has supported the study conducted in Dire Dawa, Ethiopia, and Rwanda, which reported that children who had taken deworming were more likely to recover faster compared to those who had not taken it ( 23 , 31 ). This might be because children with malnutrition are at an increased risk of infection and intestinal inflammation ( 37 ), which impair nutrient absorption and could delay the recovery time among children who had not taken deworming medication.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Children who were not dewormed were 1.87 times (AHR = 1.87, 95%CI: 1.34–2.61) more likely to recover faster than their counterparts. The finding has supported the study conducted in Dire Dawa, Ethiopia, and Rwanda, which reported that children who had taken deworming were more likely to recover faster compared to those who had not taken it ( 23 , 31 ). This might be because children with malnutrition are at an increased risk of infection and intestinal inflammation ( 37 ), which impair nutrient absorption and could delay the recovery time among children who had not taken deworming medication.…”
Section: Discussionsupporting
confidence: 83%
“…The recovery rate in the current study is also consistent with the findings of the studies done in Southern Ethiopia and rural Burkina-Faso, which reported 73% and 74.5% recovery rates (34,35), respectively. However, it is lower than the findings of the studies conducted elsewhere, for instance, 82.8% in West Arsi, Ethiopia (30), 77.5% in Rwanda (31), and 95.5 in Niger (36). This variation might be due to differences in guidance and support for TSFP among the study settings, and adherence to MAM management protocol across the regions.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation